THE INFLUENCE OF SERVICE ENCOUNTER TO CUSTOMER SATISFACTION AT PT BANK BNI (PERSERO) TBK, MANADO - Lariwu, Stevanus M.; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Entering the era of free trade, companies are expected to free increasingly fierce competition. There are many challenges and opportunities not only in domestic market but also in international markets. In anticipation of this, companies are required to work strategically using a variety of resources available to be accepted by the market. Research objectives are to examine the influence of service encounter dimension to customer satisfaction and to identify the most significant influence of service encounter to customer satisfaction at PT. Bank BNI (persero) Tbk, Manado. Service encounter itself is a direct interaction between customer and service during a period of time and customer satisfaction is an effort of a person to fulfil the expectation. This research used causal research to examine the influence of service encounter dimension to customer satisfaction and the method of analysis is multiple regression models. The population is customer of BNI Manado and sample is 100 respondents using convenience sampling. The conclusions are Service Encounter (Recovery, Civility, Adaptability, Spontaneity and Coping) have a simultaneous influence to Customer Satisfaction, and Adaptability is the most influencing factor that affect Customer satisfaction at PT Bank BNI (Persero) Tbk, Manado. Keywords: service encounter, customer satisfaction